Serat Wulangreh Pupuh Durma Sebagai Penguatan Karakter Peserta Didik di Era Modern - Parnlesta, Kesdhikawati Adwi; Sulanjari, Bambang (Universitas PGRI Semarang, 2025)
This article aims to examine the character values contained in Serat Wulangreh Pupuh Durma, a didactic Javanese literary work authored by Sri Pakubuwono IV, and to explore its relevance for character development among students in the modern era. Using a qualitative descriptive approach and hermeneutic analysis, the study investigates the moral and spiritual messages embedded in the twelve stanzas of the Pupuh Durma macapat poem. The findings reveal that Pupuh Durma embodies noble values such as self-control, personal responsibility, humility, ethical communication, social honesty, and civility. These values are highly relevant in addressing contemporary challenges faced by students, particularly in the digital age, including a lack of self-restraint, cyberbullying, hate speech, and a crisis of cultural identity. Moreover, the values in Pupuh Durma align closely with the six dimensions of the Pancasila Student Profile promoted in Indonesia's Merdeka Curriculum, and can be integrated into character education through local wisdom-based learning, such as regional language instruction, Javanese literature, and project-based character strengthening. Therefore, revitalizing traditional literary works like Pupuh Durma is essential in fostering students with strong character, deep cultural roots, and resilience to navigate modern-day challenges.